Catheter-Related Sepsis by Candida pararugosa in an Adult Patient under Chemotherapy Regimen - Gabriella Piatti; Sara Feltrin; Emanuela Fellini; Valentina Barbero; Alberto Ballestrero (Case Reports in Infectious Diseases)
Candida pararugosa is present in animals and humans in different organs and biological liquids, usually as a saprophyte. We report the case of a 61-year-old woman diagnosed with de novo stage IV metastatic lobular breast cancer, carrying a central venous catheter (port-a-cath) and bilateral stents for perirenal infiltration by malignancy. During chemotherapy regimen, a febrile episode occurred, along with a high level of serum glucan. The port-a-cath was removed after blood collection for culture, which gave isolation of Candida pararugosa strains. Given high glucan level and the patient’s frailty, empirical treatment with fluconazole was started with load-dose, 800 mg orally, at day 1 and, afterwards, with 400 mg daily for two weeks. The phenotype of susceptibility to antibiotics of the strain demonstrated lower minimal inhibitory concentration to fluconazole than that reported in the literature. The patient remained asymptomatic, and inflammation parameters showed normalization. Unfortunately, three weeks later, meningeal localization of cancer caused rapid deterioration and death.